2020
DOI: 10.1002/mp.14531
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dose and dose rate optimization (SDDRO) for FLASH proton therapy

Abstract: Purpose: FLASH radiotherapy (RT) can potentially reduce normal tissue toxicity while preserving tumoricidal effectiveness to improve the therapeutic ratio. The key of FLASH for sparing normal tissues is to irradiate Accepted Article This article is protected by copyright. All rights reserved tissues with an ultra-high dose rate (i.e., ≥40Gy/s), for which proton RT can be used. However, currently available treatment plan optimization method only optimizes the dose distribution and does not directly optimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 26 publications
0
79
0
Order By: Relevance
“…Future incorporation of spot MU into optimization could increase the proportion of UHDR delivery. Another way of achieving this would be for the optimizer to maximize high MU spots, for example by spot reduction techniques [ 2 ], or by incorporating dose-rate in the optimization [ 40 ]. We split plans depending on spot MUs to increase UHDR-metrics: by delivering higher MU spots with a higher gantry current, more dose can be delivered at UHDRs ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future incorporation of spot MU into optimization could increase the proportion of UHDR delivery. Another way of achieving this would be for the optimizer to maximize high MU spots, for example by spot reduction techniques [ 2 ], or by incorporating dose-rate in the optimization [ 40 ]. We split plans depending on spot MUs to increase UHDR-metrics: by delivering higher MU spots with a higher gantry current, more dose can be delivered at UHDRs ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Applying the current unfavorable settings (a WTP of $33,558 / QALY and a IMPT cost of $50,000), we found that for the BC patients having non-irradiated general-population cardiac risk, the costeffective scenarios existed in 40-year-old women patients who received anthracycline-based chemotherapy or special breast irradiation (IMC/SBBC). But considering the potential future trends, such as market competition, proton technology upgrades, hypofractionated schedule, the introduction of newly Chinamade compact proton treatment system, the gradual coverage of medical insurance as well as the economic growth [38,39], substantial reduction in proton cost or gradual increase in WTP may occur in the near future. Of particular note, it has been observed in our study that the cost-effective scenarios would be extended to the general-level BC patients (40-and 50-year-old women BC patients having non-irradiated general-population cardiac risk) if the current IMPT cost reduced to $20,000.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have performed pre-clinical studies using proton beams from experimental [6] and clinical accelerators [24][25][26][27]. While pre-clinical proton FLASH therapy studies to date have used passively scattered beams, new treatment planning algorithms that also optimise the high dose rate are being developed with the potential to allow proton FLASH therapy to be delivered via pencil beam scanning techniques [28,29]. Promising novel technologies such as laser particle accelerators, Very High-Energy (>100 MeV) Electron (VHEE) beams and Pluri-directional High-energy Agile Scanning Electronic Radiotherapy (PHASER) are being explored [30][31][32][33].…”
Section: Methods Of Flash Delivery and Clinical Translational Challengesmentioning
confidence: 99%